Hypertensive patients’ knowledge and practices on lifestyle modification in Extension 6, Middelburg - Amir Rahimi; Lushiku Nkombua (South African Family Practice)
Background: Hypertension (HTN) is one of the most common chronic diseases affecting the majority of patients worldwide, including in South Africa. The control of HTN and prevention of complications are major challenges for patients and healthcare workers. The proper control of the disease requires a multifactorial approach consisting of medical treatment, as well as lifestyle modification, with the assistance of healthcare workers. Addressing patients’ beliefs, the practice of lifestyle and acceptance of change are some of the ways of aiding control.